2018
DOI: 10.18202/jamal.2018.04.9030
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Motivation of Taxpayers in Using E-Filling Information Systems?

Abstract: Penelitian ini bertujuan untuk mengidentifikasi persepsi wajib pajak menggunakan e-filing dalam melaporkan Surat Pemberitahuan Tahunan (SPT) mereka. Metode yang digunakan adalah analisis Structural Equation Modeling (SEM) terhadap 100 orang wajib pajak pribadi yang terdaftar pada periode 2017 di Kantor Pelayanan Pajak Pekanbaru. Hasil penelitian ini menunjukkan bahwa para pembayar pajak berniat menggunakan e-filing jika sistem yang dirancang memberikan sejumlah kenyamanan bagi mereka. Oleh karena itu, Direktor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…By using e-Filing, taxpayers can report their SPT anytime and anywhere, 24 hours a day, seven days a week. The data in the system will then be sent to the database of the Directorate General of Taxation through ASP (Yefni et al, 2018). Thus, e-Filing is a computer system that can be used to assist users in completing and submitting annual forms of SPT.…”
Section: E-filingmentioning
confidence: 99%
“…By using e-Filing, taxpayers can report their SPT anytime and anywhere, 24 hours a day, seven days a week. The data in the system will then be sent to the database of the Directorate General of Taxation through ASP (Yefni et al, 2018). Thus, e-Filing is a computer system that can be used to assist users in completing and submitting annual forms of SPT.…”
Section: E-filingmentioning
confidence: 99%
“…Based on the findings of Sondakh (2017), it can be deduced that despite the purpose for which the government introduced the system, the taxpayers expect it to be able to fulfil the intention for which they have been used. Murniati et al (2018), in their study conducted among personal taxpayers in Pratama Pekanbaru Senapelan, found PU to maintain significant influence on the use of the e-filing system and that PU has a positive relationship with the utilisation of the e-filing. Also, in extant literature by Agarwal and Prasad (1999), they opined that taxpayers adopt the e-filing system because they have found it to be useful when filing their tax returns.…”
Section: Perceived Usefulness and Intention To Usementioning
confidence: 98%
“…Rogers (2003) delineated relative advantage as the perception of a certain innovation being better than its initial idea. E-Tax was created to provide a fast, simple, and noncomplex online channel that delivers wide-ranging tax information and services that can be easily accessed anytime, anywhere by everyone (Ibrahim 2014;Yefni et al 2018). Relative advantage and behavioral adoption/application were positively related (Ali et al 2012;Daoud and Ibrahim 2019;Zhu et al 2006).…”
Section: Relative Advantage and Intention To Adopt E-filingmentioning
confidence: 99%